Penguatan Kompetensi Guru Melalui Pendampingan Pembuatan Modul Ajar Inovatif Dengan Pendekatan Deep Learning Menggunakan Model CERDAS - Vera Rosalina Bulu; Martha Kristina Kota; Livia Eunike Paut; Habibi Musa; Juliana M. Nenohai; Sania Natonis (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2026)
This community service program aimed to strengthen the pedagogical and professional competencies of elementary school teachers through mentoring in developing innovative teaching modules based on the deep learning approach using the CERDAS model (Cermati, Eksplorasi, Rancang, Demonstrasi, Analisis, and Supervisi). The program was conducted at SMP Negeri 1 Atambua and involved 35 elementary school teachers representing 147 elementary schools in Belu Regency. The activity was implemented through collaboration between Fakultas Keguruan dan Ilmu Pendidikan Universitas Nusa Cendana and the Government of Belu Regency in response to teachers’ difficulties in designing teaching modules aligned with the Merdeka Curriculum and 21st century learning. The program employed training, discussion, guided practice, microteaching, reflection, and supervision activities integrated within the CERDAS mentoring model. The findings showed that the program positively improved teachers’ competencies in designing innovative and contextual teaching modules based on deep learning. The assessment results indicated that 50% of teacher groups achieved the “very good” category and 50% achieved the “good” category in developing teaching modules. In addition, 90% of participants stated that the program improved their understanding of the deep learning approach and HOTS-oriented learning implementation.The CERDAS model contributed to strengthening teachers’ abilities in developing active, collaborative, reflective, and problem-solving-oriented learning in accordance with the principles of the Merdeka Curriculum and 21st century education.